Navigating the US-China Trade War: Implications for Pakistan - Farooq Arshad; Muhammad Kamran Malik (Pakistan Journal of Humanities and Social Sciences, 2023)
The present study explores the implications of the trade war between the United States and China, with a focus on its security implications for Pakistan. The trade war between the world's two largest economies has resulted in escalating tariffs, trade restrictions, and increasing protectionism. As a major trading partner of both the United States and China, Pakistan finds itself caught in the crossfire of this economic conflict. From an economic standpoint, Pakistan has faced several challenges due to the trade war. The disruption in global supply chains and reduced bilateral trade between the US and China have adversely affected Pakistan's exports and foreign direct investment. Pakistan's economy heavily relies on exports to both countries, particularly in sectors such as textiles, electronics, and agriculture. Furthermore, the trade war's security implications for Pakistan are multifaceted. As tensions between the US and China have escalated, both countries have sought to gain influence and strategic advantages in various regions, including South Asia. Pakistan, being a significant player in the region, has experienced intensified competition for influence. The US has sought to deepen its partnership with Pakistan to counterbalance China's growing economic and military presence in the region, while China has expanded its investments and infrastructure projects in Pakistan under its Belt and Road Initiative. The security implications for Pakistan in the context of the trade war also involve regional dynamics. Pakistan shares a border with China and maintains a complex relationship with India, which has its own geopolitical interests in the region. The shifting alliances and power dynamics resulting from the trade war could potentially affect Pakistan's security environment and its ongoing challenges, such as the Kashmir dispute and terrorism.